A Fluorene based Fluorogenic Turn-off'' Chemosensor for the Recognition of Cu2+ and Fe3+: Computational Modeling and Living-cell Application - Elmas, Sukriye Nihan Karuk; Aydin, Duygu; Savran, Tahir; Caliskan, Eray; Koran, Kenan; Arslan, Fatma Nur; Yilmaz, Ibrahim (Bentham Science Publ Ltd, 2022)
Background: The traditional methods for the detection and quantification of Cu2+ and Fe3+ heavy metal ions are usually troublesome in terms of high-cost, non-portable, time-consuming, specialized personnel and complicated tools, so their applications in practical analyses is limited. Therefore, the development of cheap, fast and simple-use techniques/instruments with high sensitivity/selectivity for the detection of heavy metal ions is highly demanded and studied. Methods: In this study, a fluorene-based fluorescent turn-off'' sensor, methyl 2-(2-((((9H-fluoren-9-yl)methoxy)carbonyl)amino)-3- phenylpropanamido) acetate (probe FLPG) was synthesized via one pot reaction and characterized by H-1-NMR, C-13-APT-NMR, HETCOR, ATR-FTIR and elemental analysis in detailed. All emission spectral studies of the probe FLPG have been performed in CH3CN/HEPES (9/1, v/v, pH=7.4) media at rt. The quantum (Phi) yield of probe FLPG decreased considerably in the presence of Cu2+ and Fe3+. The theoretical computation of probe FLPG and its complexes were also performed using density functional theory (DFT). Furthermore, bio-imaging experiments of the probe FLPG was successfully carried out for Cu2+ and Fe3+ monitoring in living-cells. Results: The probe FLPG could sense Cu2+ and Fe3+ with high selectivity and sensitivity, and quantitative correlations (R-2>0.9000) between the Cu2+/Fe3+ concentrations (0.0-10.0 equiv). The limits of detection for Cu2+ and Fe3+ were found as 25.07 nM and 37.80 nM, respectively. The fluorescence quenching in the sensor is managed by ligand-to-metal charge transfer (LMCT) mechanism. Job's plot was used to determine the binding stoichiometry (1:2) of the probe FLPG towards Cu2+ and Fe3+. The binding constants with strongly interacting Cu2+ and Fe3+ were determined as 4.56x108 M-2 and 2.02x10(10) M-2, respectively, via the fluorescence titration experiments. The outcomes of the computational study supported the fluorescence data. Moreover, the practical application of the probe FLPG was successfully performed for living cells. Conclusion: This simple chemosensor system offers a highly selective and sensitive sensing platform for the routine detection of Cu2+ and Fe3+, and it keeps away from the usage of costly and sophisticated analysis systems.
Keywords: Fluorescence sensor; fluorene; iron; copper; DFT; bio-imaging